Comparison of scapular muscle activity during Y-raise exercise with isometric adduction in subjects with and without rounded shoulder posture. - Hwang, Byeong-Hun; Jeon, In-Cheol (Physiotherapy Theory & Practice, 2026)
Background: Rounded shoulder posture (RSP) is a commonly observed abnormal alignment of the scapula. RSP is typically associated with shortening of the pectoralis muscle and weakness of the lower trapezius (LT). Changed muscle length of these muscles may result in different movement patterns compared to healthy subjects when performing exercises. Purpose: We investigated to compare the muscle activity of the upper trapezius (UT), LT, and serratus anterior (SA) between healthy and RSP groups during Y-raise exercises with and without isometric adduction (IAD) using an elastic band. Methods: A cross-sectional study with a single data collection session, participants were classified according to the criteria for RSP and assigned to either the healthy group (25.06 ± 1.24, n = 16) or the RSP group (24.88 ± 2.09, n = 16). Surface electromyography was used to measure muscle activity of the UT, LT, and SA during the exercises. Results: UT and SA muscle activity significantly decreased during the Y-raise with IAD compared to the Y-raise without IAD in both groups (p <.025). Conversely, LT muscle activity significantly increased during the Y-raise with IAD compared to the Y-raise without IAD in the healthy group (p <.025), while LT activity significantly decreased in the RSP group (p <.025). Conclusion: Applying IAD during the Y-raise exercise is effective for selectively increasing LT activity while decreasing UT and SA activity in the healthy group. However, structural improvement of scapular alignment may be required for subjects with RSP to perform the Y-raise with IAD effectively.